USING EDUCATIONAL WEBSITES AND MOBILE APPS IN A FOREIGN LANGUAGE TEACHING PROCESS AT NON-LANGUAGE FACULTIES OF THE UNIVERSITY - Nakesheva С.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article discusses the possibilities of using educational resources of the Internet and social networks as assistants for students in the study of a foreign language at university. The current generation of students is an active user of various gadgets, social networks, digital technologies. However, the use of tools for leisure-time differs significantly from their use for training. The right choice of means of instruction contributes to the achievement of foreign language learning objectives, optimizes and influences the quality of the learning process. The author provides examples of the use of Internet resources in the educational process in traditional classes and online activities. An overview of the most frequently used sites and mobile applications with a wide range of exercises, authentic material, contributing to the formation and improvement of lexical and grammatical skills was presented.